2022
DOI: 10.1155/2022/8676787
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of 18F‐FDG‐PET/CT and 18F‐FDG‐PET/MRI in Detecting Locoregional Recurrence of HNSCC 12 Weeks after the End of Chemoradiotherapy: Single‐Center Experience with PET/MRI

Abstract: Purpose. In head and neck squamous cell carcinoma (HNSCC), the early diagnosis and efficient detection of recurrences and/or residual tumor after treatment play a very important role in patient’s prognosis. Positron emission tomography (PET) using 2-deoxy-2-18F-fluoro-D-glucose (18F-FDG) has become an established method for the diagnosis of suspected recurrence in head and neck carcinomas. In particular, integrated PET/MRI imaging that provides optimal soft tissue contrast and less dental implant artifacts com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In a retrospective study conducted on 23 patients with ACC, 18 F-FDG PET/CT added significant information to MRI and CT, detecting ACC primary sites with 87% sensitivity and upstaging 19% of patients compared to conventional imaging [176]. In another study of 36 patients with ACC, the addition or combination of 18 F-FDG-PET/CT to MRI improved the detection of local tumors and metastatic spread and was found to be beneficial in restaging [177]. 18 F-FDG PET/CT has higher sensitivity and diagnostic accuracy as compared to MRI for staging loco-regional tumor extension [177].…”
Section: Sinonasal Adenoid Cystic Carcinomamentioning
confidence: 99%
See 3 more Smart Citations
“…In a retrospective study conducted on 23 patients with ACC, 18 F-FDG PET/CT added significant information to MRI and CT, detecting ACC primary sites with 87% sensitivity and upstaging 19% of patients compared to conventional imaging [176]. In another study of 36 patients with ACC, the addition or combination of 18 F-FDG-PET/CT to MRI improved the detection of local tumors and metastatic spread and was found to be beneficial in restaging [177]. 18 F-FDG PET/CT has higher sensitivity and diagnostic accuracy as compared to MRI for staging loco-regional tumor extension [177].…”
Section: Sinonasal Adenoid Cystic Carcinomamentioning
confidence: 99%
“…In another study of 36 patients with ACC, the addition or combination of 18 F-FDG-PET/CT to MRI improved the detection of local tumors and metastatic spread and was found to be beneficial in restaging [177]. 18 F-FDG PET/CT has higher sensitivity and diagnostic accuracy as compared to MRI for staging loco-regional tumor extension [177]. In one study, the sensitivity, specificity, and accuracy of detection of local tumors on 18 F-FDG PET/CT versus MRI were reported at 96% versus 89%, 89% versus 89%, and 94% versus 89%, respectively [176].…”
Section: Sinonasal Adenoid Cystic Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Queiroz et al compared cePET/MR with cePET/CT in 87 patients with suspected recurrence of head and neck cancer and suggested that cePET/MR may be better at specifying possible tumor recurrence with obscure FDG uptake than cePET/CT(28). PET/MR has been recommended as an alternative modality to PET/CT in postchemoradiotherapy evaluation(29).Apart from tumor recurrence, distant metastasis is the primary cause of death in NPC. Zhou et al reported that the diagnostic performance of PET/MR is superior to that of PET/CT in detecting liver metastasis…”
mentioning
confidence: 99%